Nowe zasady pomocy państwa dla rolnictwa w prawie wspólnotowym - Balcerak, Sebastian (Wydawnictwo Naukowe UAM, 2007)
In the drafting o f the New Community guidelines for state aid in the agricultural and forestry sector for the years 2007-2013, the starting point for the European Commission was an assumption that economic effects o f aid granted in the agricultural sector are completely independent of their financing source. This approach is also the basis upon which legal instruments supporting the agricultural sector in member states are implemented on the same terms and conditions as those specifically set out for analogical instruments in Community law. Thus, while the Community character and the essence o f the mechanisms used to manage and streamline agricultural activities has remained untouched, the way for funds flowing from other than the Community’s resources has been paved. Therefore, in the discussion on the reform of the EU rules of state aid in agriculture, it is justified to indicate the basic assumptions of that regime. The paper aims to answer the question whether the situation of the subjects receiving support under the Common Agricultural Policy differs depending on the source of the financing instrument granted to them. The paper also touches upon the issue of a simplification of acquis communautaire in the context of the state aid rules.
NEW RULES OF STATE AID FOR AGRICULTURE IN COMMUNITY LAW